2013
DOI: 10.1074/jbc.m112.440719
|View full text |Cite
|
Sign up to set email alerts
|

Kainate Receptor Post-translational Modifications Differentially Regulate Association with 4.1N to Control Activity-dependent Receptor Endocytosis

Abstract: Background:The mechanisms that govern kainate receptor localization are poorly understood. Results: The cytoskeletal adapter 4.1N interacts with kainate receptors to promote receptor surface expression. Conclusion: Kainate receptor association with the neuronal cytoskeleton is dynamically regulated by post-translational modifications to control kainate receptor localization. Significance: Understanding the mechanisms governing kainate receptor localization may reveal how their expression is coordinated to modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 56 publications
3
47
0
Order By: Relevance
“…Several groups have investigated interactions between iGluR subunits and 4.1N, with initial evidence pointing toward the GluA1 CTD (27). Subsequent studies identified interactions with GluA4 as well as the kainate receptor subunits, GluK1 and GluK2 (28,29), but an interaction with GluA2 has not been ruled out. Intriguingly, it was recently found that posttranslational modifications to the MPR in the CTD of GluK2-a region with some sequence similarity to the AMPAR membrane-proximal CTDs-can dramatically impact association between these receptor subunits and 4.1N (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have investigated interactions between iGluR subunits and 4.1N, with initial evidence pointing toward the GluA1 CTD (27). Subsequent studies identified interactions with GluA4 as well as the kainate receptor subunits, GluK1 and GluK2 (28,29), but an interaction with GluA2 has not been ruled out. Intriguingly, it was recently found that posttranslational modifications to the MPR in the CTD of GluK2-a region with some sequence similarity to the AMPAR membrane-proximal CTDs-can dramatically impact association between these receptor subunits and 4.1N (29).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies identified interactions with GluA4 as well as the kainate receptor subunits, GluK1 and GluK2 (28,29), but an interaction with GluA2 has not been ruled out. Intriguingly, it was recently found that posttranslational modifications to the MPR in the CTD of GluK2-a region with some sequence similarity to the AMPAR membrane-proximal CTDs-can dramatically impact association between these receptor subunits and 4.1N (29). The palmitoylation of GluK2 within this membrane-proximal sequence promotes association with 4.1N, while activation of PKC and the subsequent phosphorylation of the GluK2 MPR at a serine residue proximal to a series of positively charged amino acids serves to decrease the interaction with 4.1N.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a strong base of knowledge about the activity-dependent regulation of KAR endocytosis and recycling [13,15,[67][68][69][70][71], compared to AMPARs [72] and tsVSVG cargo [73], little is known about the activitydependence of secretory pathway trafficking of KARs. A very recent study reported that secretory pathway KAR trafficking is indeed highly regulated in multiple different cellular activity contexts [48].…”
Section: Activity Dependent Secretory Pathway Traffickingmentioning
confidence: 99%
“…How GluK2‐containing KARs shape morphofunctional properties of mossy fibre synapses is unknown. GluK2/GluK5 heteromers present at mossy fibre synapses interact with proteins linked to cytoskeletal dynamics such as the β‐catenin/N‐cadherin complex (Coussen et al ., ), the cytoskeletal adapter 4.1N (Copits & Swanson, ) or CRPM2 (Marques et al ., ), and it would be interesting to know whether these interactions play a role in the morphofunctional maturation of mossy fibre synapses. It is important to point out that a loss of a functional grik2 gene, coding for GluK2, is associated with intellectual disability (Motazacker et al ., ), which could in part rely on an inappropriate maturation of synaptic circuits involved in learning and memory.…”
Section: Role Of Kars In the Developing Hippocampusmentioning
confidence: 99%